Intraoperative dexmedetomidine-induced polyuria from a loading dose: a case report. Issue 4 (April 2020) - Chen, Zhang; Chen, Ting; Ye, Haiwang; Chen, Junping; Lu, Bo
With extensive perioperative use of dexmedetomidine, there has been rising concern about its side effects, which are most commonly bradycardia and hypotension. However, increased urine output or diuresis is not well recognized with perioperative use of dexmedetomidine. We report a case of intraoperative polyuria induced by dexmedetomidine. The unusual feature of this case is that only a loading dose of dexmedetomidine was administered, but there was a long-lasting and large effect of diuresis. The findings from our case suggest that clinicians should be alert to the risk of diuresis when using dexmedetomidine.